'I expected … something': imagination, legend, and history in TripAdvisor reviews of Tintagel Castle. Issue 4 (3rd July 2020) - Hodsdon, Laura
ABSTRACT: Previous research (Orange & Laviolette [2010] A disgruntled tourist in King Arthur's court: Archaeology and identity at Tintagel, Cornwall. Public Archaeology, 9 (2), 85–107; Robb [1998] Tourism and legends: Archaeology of heritage. Annals of Tourism Research, 25 (3), 579–596) has described the interpretative tension at Tintagel Castle between history and Arthurian legend; since these articles were written, a sculpture that English Heritage says is 'inspired by the legend of King Arthur, by the historic kings and royal figures associated with Tintagel, ' and a carving of Merlin's face have been added to the site. Using discourse analysis of TripAdvisor reviews, this article explores how legend and history are experienced by visitors. Despite an 'inextricable' link with Arthur, his actual absence here in both physical and narrative realms equals an absence of imaginative stimulus, for which the statue, while enabling superficial physical interaction, cannot compensate. Likewise, many reviewers see the mediaeval remains not as a presence of ruins but an absence of castle, and are similarly uninspired to transport themselves into a historical narrative. It is only reviewers inspired by history who engage the ruins as a 'thing' whose imaginations immerse them in their visit.